2013
DOI: 10.1002/ece3.569
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of wildcat (Felis silvestris) populations in Italy

Abstract: Severe climatic changes during the Pleistocene shaped the distributions of temperate-adapted species. These species survived glaciations in classical southern refuges with more temperate climates, as well as in western and eastern peripheral Alpine temperate areas. We hypothesized that the European wildcat (Felis silvestris silvestris) populations currently distributed in Italy differentiated in, and expanded from two distinct glacial refuges, located in the southern Apennines and at the periphery of the easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 79 publications
(148 reference statements)
8
53
1
Order By: Relevance
“…The differentiation between the two wildcat clusters obtained in this study is lower than the reported F ST values by Eckert et al (2010), whereas our sampling is representative of the whole continuous distribution range, and we therefore believe that Eckert et al's F ST value is likely over-estimating genetic differentiation due to incomplete sampling (Schwartz and McKelvey 2009). Compared to other European wildcat populations, our observed F ST value is higher than the observed genetic differentiation of two bottlenecked wildcat populations in France (Say et al 2012), but in the same range of two Italian populations, which showed a divergence time similar to the end of the Last Glacial Maximum (Mattucci et al 2013). Transferred to our study, the central and western lineage might therefore display the recolonisation from different refugia: the central lineage from the Carpathian/ Alpine region, whereas for the western lineage the Iberian Peninsula is the most likely refugia (Sommer and Nadachowski 2006).…”
Section: Genetic Diversity and Substructure Within Wildcatscontrasting
confidence: 69%
See 1 more Smart Citation
“…The differentiation between the two wildcat clusters obtained in this study is lower than the reported F ST values by Eckert et al (2010), whereas our sampling is representative of the whole continuous distribution range, and we therefore believe that Eckert et al's F ST value is likely over-estimating genetic differentiation due to incomplete sampling (Schwartz and McKelvey 2009). Compared to other European wildcat populations, our observed F ST value is higher than the observed genetic differentiation of two bottlenecked wildcat populations in France (Say et al 2012), but in the same range of two Italian populations, which showed a divergence time similar to the end of the Last Glacial Maximum (Mattucci et al 2013). Transferred to our study, the central and western lineage might therefore display the recolonisation from different refugia: the central lineage from the Carpathian/ Alpine region, whereas for the western lineage the Iberian Peninsula is the most likely refugia (Sommer and Nadachowski 2006).…”
Section: Genetic Diversity and Substructure Within Wildcatscontrasting
confidence: 69%
“…Based on molecular data, domestic cats derived from Near Eastern wildcats (Felis s. lybica) and were introduced to Europe around 2000 years ago (Driscoll et al 2007;Faure and Kitchener 2009). In the past years, different rates of introgression from domestic cat alleles in the European wildcat genepool were reported, ranging from low (Mattucci et al 2013;Oliveira et al 2007) to extremely high rates of domestic cat introgression resulting in the local presence of hybrid swarms and the genetic extinction of regional populations (Beaumont et al 2001;Pierpaoli et al 2003). Nevertheless, applied marker systems as well as the number of analysed samples show a great variety among studies concerning hybridisation and this should be kept in mind when comparing hybridisation rates in different regions.…”
Section: Estimation Of Genetic Integritymentioning
confidence: 99%
“…Variable SNP loci detected in the European wildcat samples will probably represent widespread ancestral polymorphism, and chances to identify population-specific alleles will be limited. Yet, we cannot exclude that extant European wildcat populations, which probably underwent repeated cycles of demographic fluctuations due to Pleistocene climate changes (Mattucci et al, 2013), and have suffered recent population declines and fragmentation because of anthropogenic pressures, are actually less variable than domestic cats. Moreover, results obtained using other molecular markers, for example, STRs, also suggest that domestic cat may have higher genetic diversity than wildcats (for example, Pierpaoli et al, 2003;Lecis et al, 2006;Oliveira et al, 2008a, b).…”
Section: Population Variabilitymentioning
confidence: 99%
“…The survival and conservation of indigenous populations of the European wildcat might be locally threatened by introgressive hybridization with feral domestic cats (Felis silvestris catus). Over the last decade, the genotyping of highly polymorphic molecular markers (specifically microsatellites, short tandem repeats) and partial mitochondrial DNA sequences, combined with new Bayesian statistical tools, have radically improved the knowledge on wildcat population genetics and admixture with the domestic cat (for example, Beaumont et al, 2001;Randi et al, 2001;Pierpaoli et al, 2003;Kitchener et al, 2005;Lecis et al, 2006;Oliveira et al, 2008a, b;O'Brien et al, 2009;Hertwig et al, 2009;Eckert et al, 2010;Mattucci et al, 2013). Wildcats have been domesticated from African wildcat (F.s.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, this felid is present in the Eastern Sub-alps and Alps, the Central-southern Sub-Apennine and Apennine range, and Sicily (Ragni et al 2012). European wildcats and the domestic cats can live in sympatry, interbreed, and produce fertile offspring, yet hybridization is negligible and mainly occurs at the ecologic edges of wildcat populations (Lecis et al 2006;Mattucci et al 2013). This implies that where wild and domestic cats share the same ecologic niche, they may be at the same risk of infection for parasites.…”
Section: Introductionmentioning
confidence: 99%